Association of vitamin D with risk of dementia: a dose-response meta-analysis of observational studies - Huang, Yaping; Chen, Yun; Wu, Yan; Wu, Yan; Dai, Xinyi; Feng, Juan; Li, Xia (Frontiers in Neurology, 2025)
Background:The relationship between serum vitamin D levels and dementia risk remains unclear. This meta-analysis aims to evaluate the association and dose-response relationship between vitamin D levels and dementia risk.MethodsA systematic literature search was conducted in Cochrane Library, PubMed, and Embase up to October 2024. A total of 22 studies comprising 53,122 participants were included. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random-effects models. A dose–response meta-analysis explored linear and non-linear relationships.ResultsParticipants in the lowest vitamin D category had a 49% higher risk of dementia compared to those in the highest category (RR = 1.49, 95% CI: 1.32–1.67; I2 = 37.8%, p = 0.039). The dose–response analysis indicated a linear association, with each 10 nmol/L increase in vitamin D associated with a 1.2% lower dementia risk (RR = 0.988, 95% CI: 0.982–0.994; p = 0.007). Although statistically significant, the magnitude of this effect suggests limited clinical relevance at the individual level, though potential public health impact may be greater in populations with widespread deficiency. No evidence of non-linearity was observed (p for non-linearity = 0.61).ConclusionsThis meta-analysis of observational studies suggests an inverse association between serum vitamin D levels and dementia risk, with a small but consistent dose–response effect. While these findings are robust across subgroups, causality cannot be inferred from observational data. Randomized controlled trials are needed to confirm whether vitamin D supplementation can reduce dementia risk.